Ecclesiastical legal persons as NGOs participating in contractual interaction within the framework of the law against food waste - PONIATOWSKI, MICHAŁ (Prawo Kanoniczne, 2019)
In the article was presented the issue of church legal entities, which are NGOs that participate in cooperation under the Act on combating food waste. In the first part of the article was presented the form of the contract indicated in this Act, bearing in mind the additional requirements provided for in canon law. In the next part was presented the entities of this cooperation, in particular the legal definition of a non-governmental organization, which also includes church legal entities. The last part of the article concerns the subject of the contract. Contractual elements were divided into obligatory and optional elements and were described accordingly. Important conclusions were presented in the end, including de lege ferenda conclusions.